DEVELOPING MODIFIED INDONESIAN CHILDREN SONG LYRICS TO TEACH VOCABULARY TO ELEMENTARY SCHOOL THIRD GRADERS (English Education Journal, 2012)
Lagu merupakan salah satu alat edukasi yang membantu penguasaan bahasa peserta didik. Lagu menyediakan media yang menarik dan instruksional pada pembelajaran. Ini menarik karena siswa akan lebih menikmati pembelajaran. Atmosfer yang mendukung dari lagu telah membuktikan bahwa lagu merupakan media yang sangat kondusif dan efisien. Kebanyakan siswa sekolah dasar tidak dapat mengingat kosakata dengan membaca buku atau mengulang guru. Mereka akan merasa bosan dan tidak memperhatikan karena materi tidak menarik. Guru sSekolah Dasar yang menggunakan lagu  sangat membantu siswa untuk meraih full mental, potensi intelektual, dan kreatif. Karena siswa belajar melalui pengulangan dan akitifitas multi sensorik, lagu sangat membantu  dalam mengingat konsep bahasa mulai speech sampai kecakapan mendengarkan dan berbicara. Dengan menggunakan lirik lagu, diharapkan guru dapat memotivasi siswa  buntuk belajar dan memperhatikan materi yang guru sampaikan.Songs become one of the most valuable educational tools that aid the language acquisition as well as the whole learner’s physical and mental development. Song can provide attractive and instructional media in learning activities. It is attractive because the children will have more fun in learning processes. The pleasant, relaxed atmosphere fostered by songs has proven to be highly conducive to efficient learning. Most of students in elementary school are unable to memories vocabulary easily by read the textbook or by repeating the teacher. They feel bored and do not attention because the material which is presented by the teacher is not interesting and attractive. Elementary educators who add songs to the language arts classroom help students achieve their full mental, intellectual and creative potential. Because children learn best through repetition and multi-sensory activities that engage the full body, singing familiar songs and doing activities set to music help kids memorize and retain language arts concepts from parts of speech to proper listening and speaking skills. By using songs lyric during the teaching learning process, it is hoped that the teacher will be able to motivate the students to learn and pay attention to the material the teacher presents.